2018
DOI: 10.3390/ma11030385
|View full text |Cite
|
Sign up to set email alerts
|

Production of Low Cost Carbon-Fiber through Energy Optimization of Stabilization Process

Abstract: To produce high quality and low cost carbon fiber-based composites, the optimization of the production process of carbon fiber and its properties is one of the main keys. The stabilization process is the most important step in carbon fiber production that consumes a large amount of energy and its optimization can reduce the cost to a large extent. In this study, two intelligent optimization techniques, namely Support Vector Regression (SVR) and Artificial Neural Network (ANN), were studied and compared, with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 33 publications
0
9
0
2
Order By: Relevance
“…These comparisons suggested that a SVR model was a better prediction model than an ANN model, a consistent conclusion in both the training stage and the validation stage. The limited number of data caused the unexpected low performance of the ANN model [32][33][34] Therefore, the developed model can be used for estimating the number of impeller revolution for pharmaceutical formulation across different wet-mixing machines. This conclusion was consistent with the suggestion in different applications and highlighted the possible mathematical relationship between the number of impeller revolution, the properties of excipients, and the parameters of machines.…”
Section: Support Vector Regression (Svr Model)mentioning
confidence: 99%
“…These comparisons suggested that a SVR model was a better prediction model than an ANN model, a consistent conclusion in both the training stage and the validation stage. The limited number of data caused the unexpected low performance of the ANN model [32][33][34] Therefore, the developed model can be used for estimating the number of impeller revolution for pharmaceutical formulation across different wet-mixing machines. This conclusion was consistent with the suggestion in different applications and highlighted the possible mathematical relationship between the number of impeller revolution, the properties of excipients, and the parameters of machines.…”
Section: Support Vector Regression (Svr Model)mentioning
confidence: 99%
“…To make a reliable statistical test under small sample size, Design of Experiments (DOE) methods have been proposed, such as Response Surface, Taguchi and Factorial [9]. Development of DOE based on Taguchi methods to reduce industrial experimental tests requires reliable data modelling [10,11]. In some other industrial applications, large-scale data is produced, and sophisticated machine learning needs to be employed to process the data.…”
Section: Machine Learning Techniques To Model Limited or Big Datamentioning
confidence: 99%
“…[14,15] Such a long time not only results in low efficiency but also large energy consumption. [16] In addition, with the conventional heating method, the nonuniform thermal field in the PAN fiber may cause serious skin-core structure and affect the performance of the final carbon fiber. [17] Most recently, efforts have been devoted to making use of the microwave for the thermal stabilization of PAN precursors to avoids these problems.…”
Section: Introductionmentioning
confidence: 99%